Psychometric validity analysis of the indonesian version of career planning questionnaire (CPQ) on high school students: mixture rasch model approach - Febiano, Rikardus Ebed Suhartantiyo; Purwanto, Cynthia Vivian; Yudiarso, Ananta (Program Studi bimbingan Konseling PPs UNM Makassar, 2025)
This study examines the validity and reliability of the Indonesian version of the Career Planning Questionnaire (CPQ) for high school students using the Rasch Model. Data were collected via a non-random sampling survey involving 209 respondents. Analysis was conducted using Winsteps software to evaluate item quality and model fit. Results indicate that the three CPQ subscales self-knowledge, occupational knowledge, and career decision-making skills met unidimensionality criteria, with raw variance explained values of 48.1%, 42.6%, and 50.0%, respectively. Item reliability was high (0.97 for subscale A, 0.99 for B, and 0.73 for C), while person reliability was moderate (0.70, 0.42, and 0.83). Differential Item Functioning (DIF) analysis identified two gender-biased items (A16 and C20). Additionally, Mixture Rasch Model analysis revealed two latent classes, reflecting response heterogeneity among students. These findings demonstrate that the Indonesian CPQ is a valid and reliable tool for assessing high school students’ career planning, though some items require revision to enhance measurement accuracy and fairness.